Common-envelope evolution and stellar mergers - Podsiadlowski, P (2001)
We discuss the various phases encountered during common-envelope (CE) evolution, starting with the criterion for dynamical mass transfer and the onset of a common-envelope phase, the main spiralin phase and ending with the final merging of the binary components (in cases where the envelope is not ejected earlier). We emphasize the different physical processes and uncertainties in these different phases and try to clarify the main issues involved in modeling these. Results of a systematic study of the quasi-static response of a common envelope to a spiralling-in binary shed some light on the various phases and the conditions under which CE ejection may be expected. It suggests that, when the CE is ejected, the process tends to be very efficient. However, a simple energy criterion for the ejection is generally not sufficient since in many cases the spiral-in process can be self-regulating and non-dynamic. The physics of the spiral-in is fundamentally different if the initial mass donor is a radiative star. In this case, it is possible that a CE system (contact system) may become semi-detached again without experiencing significant spiral-in, and the mass loss from the contact configuration is best described by a frictionally driven stellar wind. If the spiralling-in star is compact, CE ejection may also occur when it penetrates below the convective envelope. Finally we outline a scheme, combining both quasi-static and hydrodynamical approaches, by which it can be hoped that a detailed, semi-quantitative understanding of CE evolution may be achieved in the foreseeable future.